ARM SPAN MINUS HEIGHT AND ITS RELATION TO FINAL HEIGHT IN PATIENTS WITH CONGENITAL ADRENAL HYPERPLASIA - Zainalam, Wan Alyaa Atiqah binti Wan; Hussain, Suhaimi bin; Yaacob, Najib Majd (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION This study aimed to analyse the sensitivity and specificity of arm span minus height (AS-Ht) in predicting final height outcomes in paediatric patients with Congenital Adrenal Hyperplasia (CAH) at Hospital Universiti Sains Malaysia, Kelantan. The management of CAH with glucocorticoid replacement is challenging. Undersuppression of sex hormones leads to precocious puberty and short final height while over-suppression with glucocorticoid leads to obesity and impaired growth too. Therefore, we need clinical tools to help clinicians to predict final height. Good control CAH will have near normal AS-Ht. Poor control CAH will have a high value of AS-Ht which indicates short linear height. METHODOLOGY A cross-sectional study that recruited 31 CAH patients and 78 control group participants. We analysed patients’ demographics, clinical characteristics, and auxological parameters (arm span, arm span height, midparental height). The sensitivity and specificity of AS-Ht in predicting final height were calculated. RESULT AS-Ht was significantly higher in the CAH group; (3.8 ± 3.9) compared to the control group; (1.0 ± 2.0, p<0.001). The Sensitivity and specificity of AS-Ht for predicting final height were 60.9% and 62.5%, respectively with AUC of 0.622, 95%CI (0.38,0.86). 74.2% of CAH patients had good predicted final height while 25.8% had poor final height outcome.